PELAKSANAAN JAMINAN SOSIAL TENAGA KERJA (JAMSOSTEK) BAGI PEKERJA PABRIK GARMENT DI WILAYAH PT. JAMSOSTEK CABANG UNGARAN - Andre Buwana, Srie Wiletno, Solechan (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Insurance is importen instrument for taking risk from work for daily needed. But for some low class worker is going expensive for medical treatment in hospital and for drug, if they got some accident while work company can’t cover that risk all because it’s will use much money. From that moment they got some idea to make some risk take over mechanism from worker, they call this mechanism is “Labour Insurance”. Insurance will take over all over the worker risk from sick until die when work, for the price insurance company will get what they call “premi” that worker paid with the company. Main purpose of this research is for find out procedure to claim insurance in PT. Jamsostek Cabang Ungaran, then for identify problems that show up when worker claim that insurance, at last to solve the problem that appear when they claim then insurance in PT. Jamsostek Cabang Ungaran. Method that used in this research is yuridis empiris, for the technique analysis data I use deskriptif kualitatif data that get supported by kuantitatif data. After that I will analysis the problem to get some conclusion. From the research I got some result, that many problem happen in implementation of labour insurance for garment worker in Ungaran. It’s because they don’t implement point 17 of labour act no. 3 of 1992 that concerns about social security not fully implemented by owner of the company because that many worker not protected by insurance. Worker never got their right fully protected by insurance when they work like the labor act suppose that.